Comparing between three current source circuits for using in bio electrical impedance design - Ar-Rawi, A.H.; Moghavvemi, M.; Wan-Ibrahim, W.M.A. (2009)
The current source circuit is one of the most important parts in the bioelectrical impedance devices and Bio Impedance tomography (BIT). There are many types of these circuits like (Howland, one op-amp, two op-amps, etc). In this study three types of electronic circuits are built and tested by using "Tina 7" simulation software from Texas Instrument (TI). THS4022 high speed Dual op-amps from Texas Instruments (TI) are used. The results showed that Howland circuit and one op-amp circuit are very stable up to the frequencies of 10 MHz, better than the two op-amp circuit. The two op-amp circuit is good for low frequencies with 10 KHz maximum frequency.